2019
DOI: 10.1371/journal.pone.0218545
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and drug susceptibility profiles of Mycobacterium tuberculosis obtained from Saint Peter’s TB specialized Hospital, Ethiopia

Abstract: Background Tuberculosis (TB) is one of the major public health problems in Ethiopia. Data on genetic diversity and resistance profile of circulating TB strains is critical for informing the national TB control program. Methods A cross-sectional study was conducted on 213 smear positive pulmonary TB patients between 2015 and 2016. Sputum samples were cultured on LJ media following the Petroff’s method. Region of difference-9 (RD9)-deletion typing and spoligo-typing were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
41
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 30 publications
14
41
6
Order By: Relevance
“…Among the lineages identified, lineage 4 (Euro-American lineage) was the predominant lineage comprising 79.3% of the isolates. In agreement with our finding, the Euro-American lineage was found to be the most prevalent and widespread lineage in Ethiopia [8,11,27]. This lineage is reported to be prevalent in the central highlands of Ethiopia [25,28].…”
Section: Discussionsupporting
confidence: 91%
“…Among the lineages identified, lineage 4 (Euro-American lineage) was the predominant lineage comprising 79.3% of the isolates. In agreement with our finding, the Euro-American lineage was found to be the most prevalent and widespread lineage in Ethiopia [8,11,27]. This lineage is reported to be prevalent in the central highlands of Ethiopia [25,28].…”
Section: Discussionsupporting
confidence: 91%
“…The 15.9% (11/69) drug resistant detection rate using BACTEC MGIT 960 in this study was at greater proportion than similar studies [31,32]. On the contrary, less proportion of drug resistances were reported in this study than other research reports by using the same detection system [20,33] which might be due to different study areas and sample size.…”
Section: Socio-demographic Characteristics Genotypic and Phenotypic contrasting
confidence: 71%
“…An earlier study in our country indicated that the majority of INH resistance was due to katG gene mutations which involved base changes at codon 315 (S315T1 substitution) [ 7 10 ]. In agreement with this finding, 76.9% of INH-resistant strains from Addis Ababa have a mutation at the katG gene (S315T1 substitution) revealed high-level INH resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this finding, 76.9% of INH-resistant strains from Addis Ababa have a mutation at the katG gene (S315T1 substitution) revealed high-level INH resistance. Mutation in the inhA (C15T substitution) promoter region usually reported in INH monoresistant isolates [ 8 , 10 ]. In line with this result, in our study, 30.8% of mutations in the promoter region of the inhA gene (C15T substitution) were found in the INH monoresistant isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation